Penggunaan Media MBB AR dalam Meningkatkan Kemampuan Literasi dan Karakter Siswa Slow Learner - Ardiyansah Yulinar Firdaus (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2021)
Each student has different characteristics, so different services are needed in optimizing their potential and minimizing their limitations, one of which is the slow learner. Slow learners are not stupid children, they are only slow in learning because of the obstacles and limitations they have. Slow learner also has potential that can be developed, so that special services are needed in learning, for example with the help of media that is in accordance with the problem at hand. For this reason, the authors are interested in developing media that can facilitate slow learner students at SD Negeri Sen Asen 1. This media development uses the ADDIE model design, namely analysis, design, development, implementation, and evaluation. The result of this development is in the form of MMB AR media based on Augmented reality which can be operated via a smartphone as an effort to facilitate the limitations of slow learner students in understanding whole number material. From the results of the validation, MBB AR media is very feasible to use and in its implementation, MBB AR media is very effective, because it can improve numeracy literacy in whole number material, can greatly improve digital literacy and is very good at increasing the character of self-confidence, discipline, and slow learner student cooperation.